Comparison of the efficacy of low-dose and high-dose radioactive iodine ablation in differentiated thyroid carcinoma patients post-total thyroidectomy: A systematic review and meta-analysis study - Dania, Mutia Rizka; Sahudi, Sahudi; Wihandono, Asdi (Edelweiss Applied Science and Technology, 2025)
The aim of this study is to perform a meta-analysis to compare the efficacy of low-dose and high-dose radioactive iodine ablation in patients with differentiated thyroid carcinoma post-total thyroidectomy. A systematic review was conducted following the meta-analysis study using the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) guidelines from English databases, including PubMed, Elsevier, and Sage journals. In total, 1,258 records were found, and 7 eligible articles met the inclusion criteria of the study, involving 2,164 patients. The risk of bias for this study was assessed using the Effective Public Health Practice Project (EPHPP), and all articles received a strong global rating. Low-dose radioactive iodine ablation was significantly better than high-dose radioactive iodine in differentiated thyroid carcinoma post-total thyroidectomy (Odds ratio (OR) 1.28 [95% confidence interval (CI): 1.05-1.56]; p = 0.01, I² = 24%). Low-dose radioactive iodine ablation has better efficacy than high-dose radioactive iodine ablation in patients with differentiated thyroid carcinoma post-total thyroidectomy, especially in patients with low and intermediate risk stratification according to the 2015 American Thyroid Association (ATA) guideline.